A Review on the Role of Denosumab in Fracture Prevention - Pang KL; Low NY; Chin KY (Dove Medical Press, 2020)
Kok-Lun Pang1 ,* Nie Yen Low1 ,* Kok-Yong Chin1,2 1Department of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Kuala Lumpur, Malaysia; 2State Key Laboratory of Oncogenes and Related Genes, Renji-Med X Clinical Stem Cell Research Center, Department of Urology, Ren Ji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai 200030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kok-Yong Chin Level 17, Preclinical Building, Department of Pharmacology, Faculty of MedicineUniversiti Kebangsaan Malaysia, Jalan Yaacob Latif, Bandar Tun Razak, Cheras 56000, Kuala Lumpur, MalaysiaTel +603 9145 9573Email chinkokyong@ppukm.ukm.edu.myAbstract: Denosumab is a receptor activator of nuclear factor kappa-&Bgr; ligand inhibitor, which suppresses the bone resorption process to preserve bone mass. It is usually recommended to postmenopausal women and men with high fracture risk. With the recent publication of the results from FREEDOM study and its extension, the long-term effect of denosumab in preventing fragility fractures has been put forward. This review aims at summarising the evidence of denosumab in reducing fracture risk and its safety derived from clinical studies. Most of the evidence are derived from FREEDOM trials up to 10 years of exposure. Denosumab is reported to prevent vertebral and non-vertebral fractures. It is also proven effective in Japanese women, patients with chronic kidney diseases and breast cancer patients receiving antineoplastic therapy. Denosumab discontinuation leads to high remodeling, loss of bone mineral density and increased fracture risk. These negative effects might be preventable by bisphosphonate treatment. The safety profile of denosumab is consistent with increased years of exposure. In conclusion, denosumab is a safe and effective option for reducing fracture risk among patients with osteoporosis.Keywords: bone mineral density, bone turnover marker, menopause, osteopenia, osteoporosis